Systematic analysis of SARS-CoV-2 infection of an ACE2-negative human airway cell - Puray-Chavez, Maritza (Cell Rep, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S) variants govern transmissibility, responsiveness to vaccination, and disease severity. In a screen for new models of SARS-CoV-2 infection, we identify human H522 lung adenocarcinoma cells as naturally permissive to SARS-CoV-2 infection despite complete absence of angiotensin-converting enzyme 2 (ACE2) expression. Remarkably, H522 infection requires the E484D S variant; viruses expressing wild-type S are not infectious. Anti-S monoclonal antibodies differentially neutralize SARS-CoV-2 E484D S in H522 cells as compared to ACE2-expressing cells. Sera from vaccinated individuals block this alternative entry mechanism, whereas convalescent sera are less effective. Although the H522 receptor remains unknown, depletion of surface heparan sulfates block H522 infection. Temporally resolved transcriptomic and proteomic profiling reveal alterations in cell cycle and the antiviral host cell response, including MDA5-dependent activation of type I interferon signaling. These findings establish an alternative SARS-CoV-2 host cell receptor for the E484D SARS-CoV-2 variant, which may impact tropism of SARS-CoV-2 and consequently human disease pathogenesis.